Does Immanuel Kant's categorical imperative commit him to the view that lying is always morally wrong? - Perold, Martin Ludwig (My University, 2011)
In Immanuel Kant’s essay “On a Supposed Right to Lie because of Philanthropic Concerns” (1797) he famously argues that it is never permissible to tell a lie, even when lying could save someone’s life. This view has met with a great deal of criticism from philosophers, who argue that his ethical theory must be flawed if it leads to such an undesirable conclusion. In this report, I explore this claim, arguing that this conclusion does not, after all, follow from Kant’s ethical theory. I focus in particular on the three formulations of the categorical imperative – the Formula of the Universal Law, the Formula of Humanity and the Formula of the Kingdom of Ends – and argue that none of these versions of Kant’s key ethical principle requires him to make the rigorous claim that we may never lie under any circumstances. Although lying turns out to be morally wrong in the majority of cases, based on a proper application of Kant’s theory, there are likely to be some situations in which lying is permissible or even obligatory, as I hope to show in this research.